Citizen science as a tool to increase residents’ tolerance towards urban wildlife: a case study of raccoon dogs in shanghai - Lin, Huilin; Wu, Di; Gu, Jintu (Frontiers in Environmental Science, 2024)
With the increase in the number of urban wildlife, some residents feel anxious and fearful due to the presence of wildlife in urban communities, even when there is no direct physical conflict between them. This research aims to analyze the role of citizen science in increasing residents' tolerance towards urban wildlife. This research takes the communities with the highest raccoon dog density in Shanghai as the research sites. Forty respondents were selected from local community by systematic sampling. Information was collected through semi-structured interviews and participatory observation. This research used NVivo 12 for thematic analyses. The research found that residents who did not participate in citizen science tended to take crisis observation. They regard raccoon dogs as dangerous wildlife and strictly monitor their behavior to prevent them from causing harm to humans. Residents who are engaging in citizen science tend to take scientific observations. They rationally and objectively record raccoon dogs' behavior, numbers, and distribution. Based on the experience of scientific observation, residents who had participated in citizen science anthropomorphically observed raccoon dogs in their daily lives and established an emotional bond with them. This research found that citizen science enhances residents' tolerance towards urban wildlife by producing knowledge and perceiving animal selfhood. In conclusion, this research reveals the complex relationship between residents and wildlife in urban communities by incorporating animals into sociological analysis.